Perencanaan Sistem Informasi Evaluasi Diri Menggunakan Framework Zachman - Nurdin Bahtiar (Performa: Media Ilmiah Teknik Industri, 2009)
Associated with an institutional development, self evaluation is important that cannot be separated from long-term, medium-term, or short-term strategic plans. Self-evaluation involving all the layers or elements of the institution. Information system providing self-evaluation should be made for such purpose. One approach that can be used to design self-evaluation information systems is Zachman’s framework. This framework is suitable used for developing information systems because it involves a variety of perspectives layer that looked different from the system’s perspective. This is consistent with the self-evaluation’s concept that must involve all elemens in the institution, from top management to lowest operational.